Mandatory Defence of the Accused in the Albanian Context: Between Formal Guarantee and Effective Defence - Karini, Lulzim; Aga, Eldorado (European Scientific Journal, ESJ, 2026)
This paper addresses the institution of mandatory defence of the accused in criminal proceedings as one of the fundamental guarantees of the right to a fair trial. Starting from the specific procedural position of the accused and their objective inability to exercise the right of defence effectively without professional legal assistance, the study analyses the substantive role of defence counsel as a key element in ensuring the principle of equality of arms and adversarial proceedings before an impartial court. The analysis draws on the Albanian constitutional, conventional, and criminal procedural framework, with particular focus on Article 49 of the Criminal Procedure Code. Within this framework, the 2017 amendments are of particular importance, as they not only expanded the scope of mandatory defence but also influenced the way these cases are approached and applied in practice. The paper examines in detail each case provided by law, highlighting the underlying guarantee-oriented rationale, especially in relation to the most vulnerable subjects of criminal proceedings, the seriousness of the criminal offence, and the critical stages of the process. A substantial part of the study examines the effectiveness of defence in cases involving court-appointed counsel, viewed in light of the standards developed in the jurisprudence of the European Court of Human Rights and Albanian judicial practice. In doing so, the analysis underscores the distinction between the mere formal presence of defence counsel and the genuine exercise of effective defence. Particular attention is also drawn to the absence of clear qualitative criteria governing both the selection and the ongoing oversight of court-appointed lawyers. At the same time, it is underlined that abuse of the right to defence by the accused or by defence counsel cannot constitute grounds for alleging a violation of the right to a fair trial, provided that the court has genuinely ensured the possibility of effective defence.